BONY COCHLEAR NERVE CANAL IN CHILDREN WITH BILATERAL PROFOUND SENSORINEURAL HEARING LOSS–A PILOT STUDY - Dokoska, Marija; Davcheva Chakar, Marina; Nikolova, Sonja; Kiteva Trenchevska, Gordana (Faculty of Medicine- Skopje, Ss Cyril and Methodius University in Skopje, 2021)
Introduction:The aim of this study was to evaluate the width of the bony cochlear nerve canal (BCNC) in children with congenitalsensorineural hearing loss(SNHL)and "normal" findings on thin section temporal boneCT.Materialand methods:The width of the BCNC was retrospectively evaluated in two groups of patients. The study group included 11 children (22 bone canals) aged 2-12 years, withcongenital, bilateral SNHLwho underwent cochlearimplantation (CI)from July to December 2019and no abnormalities of the inner ear were detected on their preoperative CT scans. Eleven patients (22 bone canals), aged 3-10 years, in whomno sensorineural hearing loss hadbeen diagnosed were taken as controls and CT scan of the temporal bone wasperformed for another reason -suspected acute mastoiditis, chronic otitis media, or perforation of the tympanicmembrane. Axial sections of their CT scans wereused to measure the width of the BCNC.Results:BCNC width values in patients with bilateral, profound sensorineural hearingloss rangedfrom 1.0 to 2.3 mm and the mean value was1.5±0.3 mm. In patients with normalhearing, the values for the canal width werehigher,with mean value of 2.1±0.3 mm.Conclusion: The resultsobtained showed thatthe width of the BCNC in children withbilateral, profound sensorineural hearing impairment wassignificantly smaller than in the controlgroup with normal hearing for p <0.05 (t-test=6.62912, p=0.000000).
Keywords: bony cochlear nerve canal; children; congenital sensorineural hearing loss